Czy można zabić wiarę? – Ruda Sfora Mai Lidii Kossakowskiej - Muszyńska, Katarzyna S. (Colloquia Litteraria, 2023)
The article on the example of the novel by the Polish fantasy author Maja Lidia Kossakowska, Ruda sfora, shows how the sacrum is manifested in the literary space in this genre, which values and qualities are sanctified and opposed to what. In order to build a typical for the genre’s plot – the struggle between the forces of good and evil – Kossakowska used shamanic beliefs of the Yakuts. Presenting dangers of doctrinal rationalism, she showed what the desire to extinguish the faith, may lead to, and indicate element which brings hope in the unequal fight against totalitarianism – the memory.